2021
DOI: 10.3390/foods10050964
|View full text |Cite
|
Sign up to set email alerts
|

Supply Management 2.0: A Policy Assessment and a Possible Roadmap for the Canadian Dairy Sector

Abstract: Many believe the current Canadian Dairy supply management system is outdated. Examining a recent consumer survey suggests consumers, especially among the younger generations, have mixed feelings about how the Canadian dairy industry is good for the environment or whether animals in the sector are humanely treated. The general Canadian public strongly supports financial stability for farmers, though is not fully educated about how supply management works. Issues regarding the centralization and amalgamation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…With a mean age of 20 among our sample, it is important to consider potential age-related impacts. A Canadian survey showed that of those identifying as vegetarian or vegan, more than half are under the age of 35 (Charlebois et al, 2018). This suggests that even though the vast majority of our participants did not identity as vegetarian, they are likely to know those who are or to potentially be more open to the concept.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…With a mean age of 20 among our sample, it is important to consider potential age-related impacts. A Canadian survey showed that of those identifying as vegetarian or vegan, more than half are under the age of 35 (Charlebois et al, 2018). This suggests that even though the vast majority of our participants did not identity as vegetarian, they are likely to know those who are or to potentially be more open to the concept.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…Given the growing interest in plant-based products and functional foods (Charlebois et al, 2018;Terpou et al, 2019), developing probiotic yogurt enriched with almond milk aligns with the current consumer demand for novel, health-promoting foods. As such, the primary objective of this study was to evaluate the effect of almond milk supplementation on the growth and viability of LGR-1 in yogurt samples over 6 h of fermentation and 30 days of refrigerated storage.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the increasing demand for functional foods has led to innovative incorporation of a variety of probiotic strains in to frozen desserts like cow, camel, goat and sheep milk ice cream, as well as semiripened cheese and fruit juices (Pimentel et al, 2022;Ramírez-Godínez et al, 2022;White and Hekmat, 2018). Simultaneously, the incorporation of probiotics into plant-based dairy substitutes has increased as vegan and vegetarian diet patterns gain popularity (Charlebois et al, 2018). Trends in plant-based probiotics are driven by the recognition of plant-based diets as being more environmentally sustainable than traditional diets (Melina et al, 2016), in addition to being associated with reduced risk of certain health conditions including ischemic heart disease, type 2 diabetes, hypertension, obesity and certain types of cancer (Crowe et al, 2013;Lee and Park, 2017;Jabri et al, 2021;Orlich et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Demand for dairy products has plummeted due to the closure of many businesses, creating an excess of supply which farmers are reacting to by dumping large quantities of milk. Given the unique quota system Canada has, discarding milk was not expected, unlike in other countries like the United States (Charlebois et al, 2021). This is sixth time in 55 years that Dairy Farmers of Ontario has called upon dairy farmers to dispose of raw milk.…”
Section: Supply Chain Impactsmentioning
confidence: 99%